KARAKTERISTIK STRUKTUR POPULASI TERNAK BABI DI DESA LATUHALAT KECAMATAN NUSANIWE KOTA AMBON - Joseph, Godlief; Huwae, Estalita; Rehatta, Lea M. (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The aim of this research on the structural characteristics of the pig population in Latuhalat Village is to understand the composition, dynamics and structural characteristics of the pig population in Latuhalat Village.   The parameters measured in this research are the characteristics of the respondents which consist of: age, gender, education, livelihood and population structure which includes the number of pigs per age group and the sex ratio.  The research was carried out with 40 farmers as samples and this type of research was descriptive research.  The research results show that the characteristics of respondents in the research location, Latuhalat village, Nusaniwe District, are dominated by men in productive age with secondary education and running mixed farming businesses.  The population structure of pigs is dominated by female livestock, both at calf age (50.63%), young age (51.37%) and adult age (60.53%).  This research also identified the main challenges by farmers, is the low knowledge and skills of farmers which resulted in low pig productivity.  The recommendation from this research is that there needs to be an extension program that is carried out on the government and from academics and needs to be given a technology, especially in the field of feed and housing technology.